Innovative strategies for post-stroke depression: integrating traditional Chinese medicine with neurobiological insights, including the gut-brain axis - Zhu, Lin; Han, Ruina; He, Linxia; Pan, Bingfa; Zhong, Weijie; Li, Yi; Liu, Xinru (Frontiers in Pharmacology, 2025)
Post-stroke depression (PSD) is a debilitating condition affecting more than one-third of stroke survivors, leading to significant impairments in mood, cognitive function, and overall quality of life. While conventional treatments like selective serotonin reuptake inhibitors (SSRIs) are commonly used, their efficacy is often limited, and they are associated with adverse side effects. Emerging research underscores the critical roles of neuroinflammation, neurotransmitter imbalances, and disruptions in the gut-brain axis in the development and progression of PSD, suggesting that targeting these pathways could lead to more effective therapeutic outcomes. Traditional Chinese Medicine (TCM) presents a promising multi-faceted approach, addressing these complex biological mechanisms by regulating neurotransmitter systems, modulating immune responses, and restoring gut microbiota balance. Key herbs such as Salvia miltiorrhiza Bunge (Lamiaceae; Dan Shen) and Bupleurum chinense DC. (Apiaceae; Chai Hu) have shown significant potential in modulating neurotransmitter levels, reducing neuroinflammation, and providing neuroprotection. Additionally, TCM formulations like Chaihu Shugan Powder (CSP) and Shugan Jieyu Capsules (SG) further enhance these effects by promoting gut microbiota homeostasis and restoring metabolic balance. This review delves into the biological mechanisms underlying PSD, with a particular focus on neuroinflammation, neurotransmitter dysregulation, and gut-brain axis dysfunction. It also explores the potential of integrating TCM with advanced multi-omics technologies—such as metabolomics, metagenomics, and transcriptomics—to develop personalized treatment strategies for PSD. By combining the holistic principles of TCM with modern Western medicine and cutting-edge omics technologies, this integrative approach offers a comprehensive framework for managing PSD, with the potential to significantly improve recovery outcomes and enhance the quality of life for stroke survivors.